Acute oesophageal necrosis: a rare but potentially fatal association of cocaine use. (19th July 2018) - Ullah, Waqas; Abdullah, Hafez Mohammad Ammar; Rauf, Abdul; Saleem, Kaiser
Abstract : Acute oesophageal necrosis (AON), also known as 'black oesophagus', is a rare condition characterised by the necrosis of the oesophagus usually involving the distal part. It has been associated with various conditions, and the pathogenesis is thought to involve hypovolaemia combined with decreased function of oesophageal protective mucosal barriers and may be compounded by the effect of gastric secretions on oesophageal mucosa. The hallmark of this condition is characteristic circumferential black discolouration of the distal oesophagus that may extend proximally. We present a case of a man who presented with haematemesis associated with cocaine abuse. Oesophagogastroduodenoscopy confirmed black oesophagus. The patient was managed with intravenous fluids, packed red blood cell transfusions, proton pump inhibitors and sucralfate suspension; however, he failed to recover. We have also reviewed the previous reported cases of AON in association with cocaine use.